SUCCESSFUL RATE OF GLAUCOMA SURGERY IN SECONDARY GLAUCOMA AFTER VITRECTOMY IN KARIADI HOSPITAL SEMARANG 2020-2022 - Ismail, Nur Azizah Intan Putri; Maharani, Maharani; Rahmi, Fifin L.; Puspasari, Denti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Glaucoma is one of the most frequent complications of vitrectomy surgery. It can cause a significant rise in intraocular pressure (IOP). Glaucoma surgery can be planned in medically uncontrolled glaucoma. Trabeculectomy and Glaucoma Drainage Device (GDD) implantation are the most frequent filtering surgeries used in these cases. This study aims to define the success rate of glaucoma surgery in secondary glaucoma after vitrectomy. Methods: This study is an analytical observational study with retrospective data collection held from medical records of patients with secondary glaucoma after vitrectomy who underwent glaucoma surgery in Kariadi General Hospital Semarang from 2020-2022. Surgical success defined by postoperative IOP reduced by>20% from baseline, with or without anti-glaucoma medication. Result: There were 16 eyes of trabeculectomy with 5-fluorouracil (5-FU), and 8 eyes of GDD implants. The mean preoperative IOP was 43.76+6.77 mmhg for trabeculectomy 5-FU, and 42.43+4.02 mmhg for GDD implant. IOP levels in both groups varied significantly after one day, one week, one month, and three months after surgery (p<0.05). The success rate for the trabeculectomy 5-FU group was 75% and the GDD implant group was 87.5% in 3 months. There was no statistically significant difference in the success rate between the trabeculectomy 5-FU and GDD implant groups (p=0.069). The complication were 18.75% and 25% for trabeculectomy group and GDD implant group, respectively. Conclusion: There was no significant difference in the success rate between trabeculectomy 5-FU and the GDD implant group. Both groups are viable for glaucoma surgery in secondary glaucoma after vitrectomy surgery.